The Effect Of Gender Diversity, Profitability, And Company Age On Disclosure Of Sustainability Report - Willy Sri Yuliandhari; Galuh Tresna Murti; Prajualita Tunjung Pramesthi (Jurnal Mirai Management, 2022)
A sustainability report is a report that contains the economic, environmental and social performance of a financial service institution, issuer, or public company which is then disclosed to the public. The sustainability report is the company's commitment in carrying out sustainable development that carries aspects of the triple bottom line, namely finance, environment, and society. The purpose of this study was to analyze the effect of gender diversity, profitability, and company age on the disclosure of sustainability reports in companies listed in the LQ-45 index in 2019-2021. The sample in this study was obtained using purposive sampling technique. Based on the technique that has been done, data is obtained from 20 companies within a period of three years that are consistently listed in the LQ-45 index. Then the data analysis method used in this study is the panel data regression method using Eviews 12 software. Based on the test results, the variables of gender diversity, profitability, and age of company simultaneously affect the disclosure of sustainability reports in companies listed in the LQ-45 index for 2019-2021. Then partially profitability and age of company positifly on the disclosure of sustainability reports on companies. While the gender diversity has no effect on the disclosure of sustainability reports in companies. Based on the results of the study, it is recommended for further researchers to use different variables and the research period with the latest time. And for the company, it is recommended to maintain the profits earned to improve programs and disclosure of environmental and social performance. Thus, it can certainly increase the confidence of external parties to increase the value and performance of the company. Kata Kunci: Company age, disclosure of sustainability reports, gender diversity, profitability